20·30대 여성의 체형 과대인식에 따른 체중조절행위, 삶의 질, 식행동 및 영양소 섭취상태: 2010-2011년 국민건강영양조사 자료 이용 - 박슬기; 현태선; 이홍미; Park, Seulki; Hyun, Taisun; Lee, Hongmie (Korean journal of community nutrition, 2015)
Objectives: This study was performed to investigate the effects of overestimation of their own body shape on weight control behaviors, mental condition, physical activity, dietary behavior, health-related quality of life, and nutritional status among young Korean females. Methods: A total of 1,514 women aged 20-39 years who are not pregnant and lactating among those who participated in the Fifth Korea National Health and Nutrition Examination Survey (2010~2011), were analyzed and grouped into underestimation (n=120), normal estimation (NE, n=840), and overestimation (OE, n=554), based on their body perception compared to actual percent ideal body weights. Variables were compared between OE group and NE group. Results: The subjects in OE group were significantly younger (29.5 vs. 30.5 years, respectively p < 0.05) and had lower body mass index (20.9 vs. 22.2 respectively, p < 0.01), health-related quality of life measured by EQ-5D (EuroQol-5 Dimension)(0.97 vs. 0.98 respectively, p < 0.05), nutrition adequacy ratio (NAR) of protein (0.91 vs. 0.93 respectively, p < 0.05), phosphorous (0.93 vs. 0.96 respectively, p < 0.05), and iron (0.70 vs. 0.75 respectively, p < 0.01), and index of nutrition quality (INQ) of iron (0.84 vs. 0.89 respectively, p < 0.05) compared to those in the NE group. The results of logistic regression showed that unmarried status (OR 1.32; 1.01~1.72) and severely underweight/underweight status (OR 1.94; 1.01~3.75)/(OR 1.81; 1.34~2.45) were significantly related to the probability of overestimation by the subjects. Significantly more women in OE group practiced fasting, skipping meals, and taking prescribed pills to lose body weights and had skipped breakfast compared to those in the NE group. Conclusions: The results of this study suggested that the Korean young women's distorted perception of own body shape may be associated with undesirable weight control behavior, low quality of life, and lower nutritional status. Therefore, nutrition education for this group should include information on correct body shape perception and its importance.